1985
DOI: 10.1111/j.1755-3768.1985.tb01528.x
|View full text |Cite
|
Sign up to set email alerts
|

A Fukuyama type of congenital muscular dystrophy associated with atypical gyrate atrophy of the choroid and retina: A case report

Abstract: A three-year-ten-month old boy with the Fukuyama type of congenital muscular dystrophy (FCMD), early onset of muscular hypotonia, severe mental retardation, a slow progressive course and a characteristic fundus appearance similar to that of gyrate atrophy is described. Hyperornithinaemia and iminoglycinuria were not noted. To our knowledge, this is the first reported case of FCMD associated with atypical gyrate atrophy of the choroid and retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The patient had iminoglycinuria but no hyperornithinaemia. Recently, Mishima et al (1985) reported on a case of Fukuyama type of congenital muscular dystrophy with a fundus picture resembling GA. Neither hyperornithinaemia nor iminoglycinuria was found.…”
Section: Discussionmentioning
confidence: 99%
“…The patient had iminoglycinuria but no hyperornithinaemia. Recently, Mishima et al (1985) reported on a case of Fukuyama type of congenital muscular dystrophy with a fundus picture resembling GA. Neither hyperornithinaemia nor iminoglycinuria was found.…”
Section: Discussionmentioning
confidence: 99%
“…3 Most Japanese patients with XLOA have brown irides that show no translucency, nonalbinotic fundi with moderate pigmentation, and normal skin and hair color. 4 However, the iris in our patient was light brown and the fundus was albinotic. His hair color was mostly light brown, and his skin color was fair for a Japanese individual.…”
Section: Case Of a Japanese Patient With X-linked Ocular Albinism Assmentioning
confidence: 95%
“…3,4 We describe an infant with FCMD exhibiting a severe form of ocular phenotype and LETTERS negative-type ERG under dark-adapted conditions, a fi nding that to our knowledge has not been reported before.…”
mentioning
confidence: 90%